2023
DOI: 10.1186/s13059-023-02929-6
|View full text |Cite
|
Sign up to set email alerts
|

Boosting genome editing efficiency in human cells and plants with novel LbCas12a variants

Abstract: Background Cas12a (formerly known as Cpf1), the class II type V CRISPR nuclease, has been widely used for genome editing in mammalian cells and plants due to its distinct characteristics from Cas9. Despite being one of the most robust Cas12a nucleases, LbCas12a in general is less efficient than SpCas9 for genome editing in human cells, animals, and plants. Results To improve the editing efficiency of LbCas12a, we conduct saturation mutagenesis in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Lachnospiraceae proteins that have been applied as molecular tools in other organisms are strong candidates to advance genome engineering in Lachnospiraceae . For example, LbCas12a, which was isolated from Lachnospiraceae bacterium ND 2006 ( Tak et al, 2017 ), has been applied for genome editing in eukaryotes including fungi ( Chen T. et al, 2023 ), plants ( Kim et al, 2021 ), flies ( Port et al, 2020 ), and human cells ( Zhang et al, 2023 ). Another Cas12a variant, Lb2Cas12a, derived from Lachnospiraceae bacterium MA 2020, has been developed to have enhanced editing activity and broadened protospacer adjacent motif (PAM) recognition in human cells ( Tran et al, 2021 ).…”
Section: Cultivation and Engineeringmentioning
confidence: 99%
“…Lachnospiraceae proteins that have been applied as molecular tools in other organisms are strong candidates to advance genome engineering in Lachnospiraceae . For example, LbCas12a, which was isolated from Lachnospiraceae bacterium ND 2006 ( Tak et al, 2017 ), has been applied for genome editing in eukaryotes including fungi ( Chen T. et al, 2023 ), plants ( Kim et al, 2021 ), flies ( Port et al, 2020 ), and human cells ( Zhang et al, 2023 ). Another Cas12a variant, Lb2Cas12a, derived from Lachnospiraceae bacterium MA 2020, has been developed to have enhanced editing activity and broadened protospacer adjacent motif (PAM) recognition in human cells ( Tran et al, 2021 ).…”
Section: Cultivation and Engineeringmentioning
confidence: 99%
“…Previous studies showed Cas12a orthologs and engineered Cas12a had low off-target effects ( Zhang et al, 2021b ; Zhang et al, 2023 ). To further verify this feature of Cas12a, we analyzed off-target effects of both Ev1Cas12a and Hs1Cas12a in poplar T 0 plants.…”
Section: Resultsmentioning
confidence: 99%
“…So far, multiple Cas12a nucleases have been demonstrated in plants, including AsCas12a, LbCas12a ( Tang et al, 2017 ), FnCas12a ( Zhong et al, 2018 ), ErCas12a (also known as MAD7) ( Lin et al, 2021 ), and Mb2Cas12a ( Zhang et al, 2021b ). Moreover, researchers have improved genome editing efficiency of Cas12a through protein engineering, such as LbCas12a-D156R/ttLbCas12a ( Schindele and Puchta, 2020 ), AsCas12a ultra ( Zhang et al, 2021a ), intron-containing ttLbCas12a ( Schindele et al, 2023 ), LbCas12a-RV and LbCas12a-RRV ( Zhang et al, 2023 ). Nevertheless, the temperature sensitivity of Cas12a represents a constraint that affects Cas12-mediated genome editing ( Malzahn et al, 2019 ; Zhang et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of K172R, additional contacts with the backbone of the DNA in the PAM‐proximal region as well as additional hydrogen bonds with the base at the 3′ end of the PAM might form. The resulting enhanced editing efficiency is in line with results from other studies, which showed that non‐negatively charged amino acids within DNA‐interacting protein domains increase editing activities of different Cas12a orthologues, probably due to improved DNA binding (Zhang et al ., 2021b , 2023 ). However, it should be kept in mind that this structure only reflects a probable model of Er Cas12a and that the crRNA/DNA duplex was only visually inserted into the model, based on the analogous As Cas12a.…”
Section: Discussionmentioning
confidence: 99%
“…Can the cutting efficiency of imErCas12a be further improved? This will most probably be the case as the example of LbCas12a demonstrates: Recently, besides the already known activity enhancing mutation D156R (Schindele and Puchta, 2020 ), two other mutation could be identified by saturation mutagenesis, that in combination resulted in the variant LbCas12a‐RRV showing a further increase of editing efficiency (Zhang et al ., 2023 ). On the other hand, the integration of introns in the ORF of ttLbCas12a lead to drastic enhancement of gene editing and gene targeting frequencies (Schindele et al ., 2023 ).…”
Section: Discussionmentioning
confidence: 99%